Notes on Quadratic Programming: The Kuhn-Tucker and Theil-Van De Panne Conditions, Degeneracy, and Equality Constraints - Boot, J. C. G. (Management Science, 1961)
The purpose of this note is to prove that the rules on which Theil and van de Panne [Theil, H., C. van de Panne. 1960. Quadratic programming as an extension of conventional quadratic maximization. Management Sci. 7(1) 1–20] based their recent method to follow straightforward from the well-known Kuhn-Tucker conditions and to propose a method for handling degeneracy in quadratic programming.